2021
DOI: 10.1155/2021/2337818
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppresses EMT in Liver and Gastric Carcinoma Cells through Combination with TGFβR Regulating TGF‐β/Smad Pathway

Abstract: Berberine (BBR), a natural alkaloid derived from Coptis, has anticancer activity. Some researchers have found that it could restrain epithelial-mesenchymal transition (EMT) of melanoma, neuroblastoma, and other tumor cells. However, it is unclear whether BBR can reverse EMT in hepatocellular carcinoma (HCC) and gastric carcinoma (GC). In our study, BBR inhibited the migration and invasion of HepG2, MGC803, and SGC7901 cells in a dose-dependent manner. Transcription sequencing assays showed that Vimentin, MMP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“… 20 Berberine also suppressed the EMT in hepatocellular carcinoma and gastric carcinoma cell lines by upregulating p-SMAD2 and downregulating p-SMAD3. 21 However, the relationship between berberine and the TGF-β/SMAD signaling pathway in glioma is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Berberine also suppressed the EMT in hepatocellular carcinoma and gastric carcinoma cell lines by upregulating p-SMAD2 and downregulating p-SMAD3. 21 However, the relationship between berberine and the TGF-β/SMAD signaling pathway in glioma is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As a natural molecule, BBR has been demonstrated in the bit proliferation and metastasis of various cancers [ 7 , 8 , 9 , 10 , 27 ]. However, previous research on BBR in BRCA cells was limited to verifying known oncogenic pathways and targets, and the critical information for drug development was missing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BBR showed good antitumor activity. Several types of cancer cells are directly affected by it [ 7 , 8 , 9 , 10 ]. However, as with many natural therapeutic products, there is a lack of high-quality scientific evidence regarding the core pathways and targets of BBR.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments showed that CPT, DMC, ART, SNP and BER increased E-cadherin expression, decreased expression of Vimentin and α-SMA, enhanced cell adhesion and weakened cell migration. CPT, ART and BER have been previously reported to inhibit the EMT [ 33 , 34 , 35 ]. Identification of the inhibitory actions of DMC and SNP on the TGF-β1-induced EMT in A549 cells is a novel finding.…”
Section: Discussionmentioning
confidence: 99%